PTU-227 Statins may modify colorectal anastomotic leak risk in high risk patients. (22nd June 2015) - Battersby, CLF; Green, P; Vyapury, V; Rooney, P; Hunt, J
Abstract : Introduction: Anastomotic leak is one of the most feared complications of colorectal surgery, as it is associated with increased morbidity and mortality, need for a permanent stoma and recurrence of cancer. Statins are amongst the most commonly prescribed drugs in the developed world. Patients taking statins would be expected to have comorbidities associated with an increased risk of anastomotic leak. A small number of studies investigating the effect of statins upon anastomotic leak have yielded conflicting results. Statins are known to affect the inflammatory response, white cell function, endothelial function and angiogenesis, all of which are fundamental to tissue healing; therefore statins may influence anastomotic healing. We aimed to explore the link between statins and anastomotic leaks in our practice. Method: A prospectively maintained database of patients undergoing surgery requiring primary anastomosis, for both benign and malignant disease, in a single-centre teaching hospital was created. Information was collected on patient demographics, medications, pre-operative blood results, ASA and post-operative course. Group comparisons were performed using Mann-Whitney U test and Fisher's Exact test. Results: 114 patients (64 male). Median age 66 years (Interquartile range 56–74 years). 6 (5%) patients had radiologically confirmed anastomotic leak. 45 (39.4%) patients were taking statins pre-operatively. Statins were not associated with reduced risk of anastomotic leak. Pre-operative eGFR (p = 0.018) and maximum 7-day CRP (p = 0.003) were significant predictors of anastomotic leak. ASA in patients on statins was significantly higher than patients not taking statins (p < 0.001), however, there was no significant difference in ASA between patients who leaked and those who did not. Conclusion: Patients with comorbidities, reflected by higher ASA scores, are known to have an increased risk of colorectal anastomotic leak. In this cohort of patients, with a higher rate of statin use than the UK population, we have shown that although patients taking statins did not have a significantly reduced leak risk compared to non statin users, high risk patients taking statins had the same leak risk as non-high risk patients, therefore it is plausible that statins normalise the risk of anastomotic leak in high risk patients. Disclosure of interest: None Declared. References: Singh PP, Srinivasa S, Bambarawana S, Lemanu DP, Kahokehr AA, Zargar-Shoshtari K, et al . Perioperative use of statins in elective colectomy. Dis Colon Rectum 2012;55(2):205–10 Bisgard AS, Noack MW, Klein M, Rosenberg J, Gogenur I. Perioperative statin therapy is not associated with reduced risk of anastomotic leakage after colorectal resection. Dis Colon Rectum 2013;56(8):980–6